A framework to make charity collection transparent and auditable using blockchain technology. (May 2020) - Farooq, Muhammad Shoaib; Khan, Misbah; Abid, Adnan
Abstract: Charity is considered as a moral obligation throughout the world, and a huge amount of money comes into circulation in the name of charity. In most of the cases, the charity collection processes are not transparent, and due to this the charitable organizations struggle to gain donors' trust and interest. This article presents a blockchain-based charity management platform that aims to provide a transparent, secure, auditable, and efficient system. The proposed platform comprehensively covers charity collection process using crypto wallets, Initial Coin Offering (ICO), economic model, and introduces CharityCoin (CC) as a digital currency. Furthermore, smart-contracts for pertinent use cases have also been provided, which include exchanging fiat currency to CC, buying and selling CC, transferring CC to organizations and individuals, and call for donations. Finally, the performance evaluation shows that proposed architecture scales well for large data size.